2020
DOI: 10.1016/j.tibtech.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Process Analytical Technologies and Data Analytics for the Manufacture of Monoclonal Antibodies

Abstract: Process analytical technology (PAT) for the manufacture of monoclonal antibodies (mAbs) is defined by an integrated set of advanced and automated methods that analyze the compositions and biophysical properties of cell culture fluids, cell-free product streams, and biotherapeutic molecules that are ultimately formulated into concentrated products. In-line or near-line probes and systems are remarkably well developed, although challenges remain in the determination of the absence of viral loads, detecting micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 65 publications
0
42
0
1
Order By: Relevance
“…The upstream production of mAbs in CHO cells is widely conducted using suspension cultures in stirred tank bioreactors under different modes: batch, fed-batch, and perfusion (continuous culture with retention of cells), although in the process of increasing the cell number (inoculum train) to reach the production volume, other types of bioreactors are also used, such as shake flasks and wave bioreactors, with preference for single-use systems [ 267 , 282 ]. While, the production Nbs bioprocesses can be carried out in bacterial or yeasts conventional biopharmaceutical plants, where the inoculum train and the production bioreactors are generally made of stainless steel, with economical culture media, implying larger industrial scales than those of animal cells.…”
Section: Remarks On the Production Of Mabs For Covid-19 Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The upstream production of mAbs in CHO cells is widely conducted using suspension cultures in stirred tank bioreactors under different modes: batch, fed-batch, and perfusion (continuous culture with retention of cells), although in the process of increasing the cell number (inoculum train) to reach the production volume, other types of bioreactors are also used, such as shake flasks and wave bioreactors, with preference for single-use systems [ 267 , 282 ]. While, the production Nbs bioprocesses can be carried out in bacterial or yeasts conventional biopharmaceutical plants, where the inoculum train and the production bioreactors are generally made of stainless steel, with economical culture media, implying larger industrial scales than those of animal cells.…”
Section: Remarks On the Production Of Mabs For Covid-19 Treatmentmentioning
confidence: 99%
“…In the case of mammalian cells, the aim is usually to keep the shear forces or oxygen transfer constant [ 283 ]. Moreover, technological, analytical, and regulatory advances promote biopharmacies to implement continuous culture systems to meet the growing demand for mAb production [ 275 , 282 , 284 ]. mAb isolation and purification (downstream) represent a significant portion of the production effort and costs [ 270 , 285 ].…”
Section: Remarks On the Production Of Mabs For Covid-19 Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the addition of an autosampler adds the additional benefits of previously at-line analysis, such as ELISA, MS, and/or any other complex analysis techniques [22,24]. Though the inlet and outlet PAT provide the critical data to the controller unit necessary for fractionation control, PAT are also utilised to monitor the fouling of the column.…”
Section: The Future Of Industrial Chromatography Control Systemsmentioning
confidence: 99%
“…For these reasons, a major focus in industry has been to improve the process efficiency and robustness of chromatography through the implementation of process monitoring and control using PAT. However, while the ability of these PAT to monitor processes has been demonstrated in research and process development, the number of demonstrated implementations of control strategies utilising PAT is significantly lower [21][22][23][24]. This indicates a gap in meeting all the objectives of the FDA initiative.…”
Section: Introductionmentioning
confidence: 99%